Detection of Fusion Genes Using a Targeted RNA Sequencing Panel in Gastrointestinal and Rare Cancers. (22nd January 2020) - Lee, Su Jin; Hong, Jung Yong; Kim, Kyung; Kim, Kyoung-Mee; Kang, So Young; Lee, Taeyang; Kim, Seung Tae; Park, Se Hoon; Park, Young Suk; Lim, Ho Yeong; Kang, Won Ki; Lee, Jeeyun; et al.
Abstract : Successful identification and targeting of oncogenic gene fusion is a major breakthrough in cancer treatment. Here, we investigate the therapeutic implications and feasibility of using a targeted RNA sequencing panel to identify fusion genes in gastrointestinal and rare cancers. From February through December 2017, patients with gastrointestinal, hepatobiliary, gynecologic, sarcoma, or rare cancers were recruited for a clinical sequencing project at Samsung Medical Center (NCT #02593578). The median age of the patients was 58 years (range, 31–81 years), and the male-to-female ratio was 1.3 : 1. A total of 118 patients passed the quality control process for a next-generation sequencing- (NGS-) based targeted sequencing assay. The NGS-based targeted sequencing assay was performed to detect gene fusions in 36–53 cancer-implicated genes. The following cancer types were included in this study: 28 colorectal cancers, 27 biliary tract cancers, 25 gastric cancers, 18 soft tissue sarcomas, 9 pancreatic cancers, 6 ovarian cancers, and 9 other rare cancers. Strong fusion was detected in 25 samples (21.2%). We found that 5.9% (7/118) of patients had known targetable fusion genes involving NTRK1 (n = 3 ), FGFR (n = 3 ), and RET (n = 1 ), and 10.2% (12/118) of patients had potentially targetable fusion genes involving RAF1 (n = 4 ), BRAF (n = 2 ), ALK (n = 2 ), ROS1 (n = 1 ), EGFR (n = 1 ), and CLDN18 (n = 2 ). Thus, we successfully identified a substantial proportion of patients harboring fusion genes by RNA panel sequencing of gastrointestinal/rare cancers. Targetable and potentially targetable involved fusion genes were NTRK1, RET, FGFR3, FGFR2, BRAF, RAF1, ALK, ROS1, and CLDN18 . Detection of fusion genes by RNA panel sequencing may be beneficial in refractory patients with gastrointestinal/rare cancers.